Vidia and the fairy crown - Driscoll, Laura; Clarke, Judith; Disney Storybook Artists (New York : Random House Children's Books, 2006)
When Vidia, a disagreeable fairy, finds herself accused of stealing the Queen's tiara, she enlists the aid of a fellow sprite to help investigate and the two race against time to clear Vidia's name.
"A Stepping Stone book."
4.2
3-6
3-6
School Library Journal
660
Keywords: Fairies -- Juvenile fiction; Theft -- Juvenile fiction; Lost articles -- Juvenile fiction; Fairies -- Fiction; Stealing -- Fiction; Lost and found possessions -- Fiction; Fairies -- Fiction; Lost and found possessions -- Fiction; Theft -- Fiction